Sleep difficulties and their impact on recovery following mild traumatic brain injury in children. (23rd August 2016) - Theadom, Alice; Starkey, Nicola; Jones, Kelly; Cropley, Mark; Parmar, Priya; Barker-Collo, Suzanne; Feigin, Valery L.
Abstract: Objective : To determine the frequency of sleep difficulties in children following mild traumatic brain injury (TBI) over time and explore the role of sleep on recovery and behaviour. Methods : Longitudinal study of 109 children aged between 8–16 years who had experienced a mild TBI, with an embedded case control study. Parents completed assessments of the child's sleep quality, symptoms and behaviour at baseline, 1, 6 and 12 months post-injury. Regression analyses explored the impact of poor sleep on 12-month outcomes. Healthy control children were assessed at one time point for comparison to determine the longer-term impact of brain injury on sleep. Results : The number of children experiencing poor sleep quality peaked 1-month post-injury (39%), reducing to 28% 12-months post-injury. Poor sleep quality at 1-month was associated with increased frequency and severity of symptoms and poorer behavioural outcomes 1 year post-TBI. Cases with TBI were significantly more likely to have sleep difficulties 1-year post-injury than controls (Odds ratio = 3.09). Conclusions : Sleep difficulties are common following mild TBI in children and are predictive of longer-term outcomes. Identifying children with sleep difficulties post-injury and providing support to facilitate sleep may improve their longer-term functioning.